2021
DOI: 10.1080/22221751.2021.1937327
|View full text |Cite
|
Sign up to set email alerts
|

Resistance evolution of hypervirulent carbapenem-resistant Klebsiella pneumoniae ST11 during treatment with tigecycline and polymyxin

Abstract: Hypervirulent carbapenem-resistant Klebsiella pneumoniae (hv-CRKP) has recently aroused increasing attention, especially ST11, the predominant CRKP clone in China.Here, we report a case of hv-CRKP-associated infection and reveal the in-host evolution of its mechanism of resistance to tigecycline and polymyxin under clinical therapy. A total of 11 K. pneumoniae carbapenemase (KPC)-producing CRKP strains were consecutively isolated from a male patient who suffered from continuous and multisite infections and suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(46 citation statements)
references
References 53 publications
0
46
0
Order By: Relevance
“…Among them, 16 CRKP isolates harbored the bla KPC-2 gene, representing a potential clonal spread due to their similar PFGE patterns. In silico MLST analysis identified all the 16 KPC-2-producing CRKP isolates as ST11, which is the most predominant sequence type of KPC-2-producing CRKP in China and has been reported worldwide, including America, Europe, and Asia (Baraniak et al, 2011;Jiang et al, 2015;Zhan et al, 2017;Gu et al, 2018;Ko, 2019;Spencer et al, 2019;Zhou et al, 2020;Jin et al, 2021;Yang et al, 2021). Moreover, all the 16 KPC-2-producing CRKP isolates belonged to the serotype KL64, which differs from those reported previously, such as KL1, KL2, and KL62 (Feng et al, 2018;Gu et al, 2018).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Among them, 16 CRKP isolates harbored the bla KPC-2 gene, representing a potential clonal spread due to their similar PFGE patterns. In silico MLST analysis identified all the 16 KPC-2-producing CRKP isolates as ST11, which is the most predominant sequence type of KPC-2-producing CRKP in China and has been reported worldwide, including America, Europe, and Asia (Baraniak et al, 2011;Jiang et al, 2015;Zhan et al, 2017;Gu et al, 2018;Ko, 2019;Spencer et al, 2019;Zhou et al, 2020;Jin et al, 2021;Yang et al, 2021). Moreover, all the 16 KPC-2-producing CRKP isolates belonged to the serotype KL64, which differs from those reported previously, such as KL1, KL2, and KL62 (Feng et al, 2018;Gu et al, 2018).…”
Section: Discussionmentioning
confidence: 64%
“…Moreover, all the 16 KPC-2-producing CRKP isolates belonged to the serotype KL64, which differs from those reported previously, such as KL1, KL2, and KL62 (Feng et al, 2018;Gu et al, 2018). However, an infection caused by KPC-2producing ST11-KL64 CRKP was frequently reported recently (De Campos et al, 2018;Jia et al, 2019;Ruan et al, 2020a;Zhang et al, 2020b;Zhou et al, 2020;Jin et al, 2021;Yang et al, 2021). Zhou et al (2020) reported that patients infected by ST11-KL64 CRKP had a significantly higher mortality rate than those infected by other CRKP.…”
Section: Discussionmentioning
confidence: 75%
“…We previously searched the PubMed database for reports on colistin-resistant CR-hvKP, and to the best of our knowledge, only five papers describing colistin-resistant CR-hvKP had been published. In addition, the majority of instances of reported colistin-resistance were attributable to changes in the mgrB gene, including IS element mutations such as the insertion of IS Kpn18 or IS Kpn26 ( Dong et al, 2018 ; Huang et al, 2018 ; Solgi et al, 2020 ) and chromosomal mutations such as Q30stop and C39F ( Shelenkov et al, 2020 ; Jin et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated that colistin has excellent in vitro activity against CR-hvKP strains ( Yu et al, 2018 ; Hao et al, 2020 ; Lin et al, 2020 ). However, cases of colistin-resistant CR-hvKP are increasing in clinical practice in China ( Dong et al, 2018 ; Huang et al, 2018 ; Solgi et al, 2020 ; Jin et al, 2021 ). The common mechanisms mediating colistin resistance in K. pneumoniae include chromosomal mutation of the genes associated with the modification of lipid A, such as those encoding the enzymes involved in lipid A synthesis and the PmrAB and PhoPQ two-component systems ( Hamel et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…We searched the PubMed database using the terms ā€œcarbapenem-resistant hypervirulent K. pneumoniae ā€ OR ā€œcarbapenemase-producing hypervirulent K. pneumoniae ā€ AND ā€œtigecyclineā€ for articles published up to 1 June 2021 with no language restrictions. Only nine papers were found, four of which were on tigecycline nonsusceptible CR-hvKP, with the majority being identified in ST11 CR-hvKP strains ( 13 ā€“ 15 ). Here, we report the carriage of the carbapenemase gene bla IMP-4 in two K2-ST65 hypervirulent K. pneumoniae isolates in China, and notably, one of them demonstrated reduced tigecycline susceptibility mediated by an efflux pump.…”
Section: Introductionmentioning
confidence: 99%